A study on the workplace cultural violence against nurses: a systematic review and meta-analysis - Masoumeh Shohani; Hamed Tavan (Systematic Reviews)
Abstract Introduction Cultural violence includes any offensive behavior regarding ethnicity, race, language, religion, and place of birth devaluing human dignity. The purpose of this study was to investigate workplace cultural violence against nurses by systematic review and meta-analysis. Materials and methods The guideline of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was followed. The search was independently conducted in ISI, Cochrane Library, Google Scholar, PubMed, and Scopus by two researchers. We used mesh keywords to recruit publications from different regions of the world between 2002 and 2017. Data was analyzed using meta-analysis and STATA software. To determine the heterogeneity, Q and I 2 indices were used. Results A total of 50 articles were found from which 8 were ultimately included in the systematic review process. The overall rate of workplace cultural violence among nurses was 17.25% (95% CI 16.83–17.66, I 2 = 99.7%, P = 0.0001). Also, the rate of workplace cultural violence against nurses and patients’ relatives and companions was 8.21% (95% CI 7.61–8.81, I 2 = 99.7%, P = 0.0001). The meta-regression of cultural violence in terms of sample size and year of study rendered a significant decrease in the violence rate by increasing years and sample size (P < 0.001). Conclusion Although not all cases of cultural violence are reported and recorded, the rate of cultural violence against nurses is decreasing according to the results of our study. Nevertheless, by providing good services and appropriate education to patients, the overall incidence of cultural violence is expected to be further reduced.